Mediastinitis due to Odontogenic infection - Zainul Cholid; Yuliana Arina (ziauddin University, 2024)
Mediastinitis due to the spreading of odontogenic infection is rare, but the mortality rate is high. This report presents the case of mediastinitis caused by the spreading of odontogenic infection in healthy males. The patient complained of dyspnoea and trismus. The diffuse and fluctuating swelling was observed in the submandibular and submental area, which spreads to the neck and chest. It was diagnosed mediastinitis as a submandibular and submental abscess complication due to the impacted teeth' pericoronitis. Two drainage incisions were made following the administration of oxygen and antibiotics injection. The success of mediastinitis treatment due to the spread of odontogenic infection is determined by proper diagnosis and appropriate initial management. Antibiotic administration and pus drainage are the very decisive stage of treatment to reduce the risk of death. It is necessary to eliminate the causative of odontogenic infection.